Synthesis of new glucosylated derivatives of 1,4-quinones - O. P. Bondarchuk (Zaporozhye State Medical University, 2014)
Aim. In order to obtain a number of drug-like molecules as potential intercalators of RNA and DNA a series of synthetic compounds of similar structure and biological effects with known analogues of natural 1,4-quinones derivatives have been synthesized. Methods and results. New glycosylated derivatives of 1,4-quinones have been studied, simple and convenient preparative methods for obtaining new 2-(3)-glyucosylamino-5-R-3(2)-chloro-1,4-naphthoquinones based on nucleophilic substitution of chlorine atom on glyucosylaminic fragment have been developed. The structure of compounds and their physical and chemical parameters have been determined. The introduction of glyucosylaminic fragment in 1,4-quinone molecule leads to decrease of toxicity and increase of water solubility of synthesized compounds. Conclusion. This suggests the possibility of using a larger range of substances dosage in in vivo studies and better bioavailability of synthesized compounds.